HUNTING DISTRICT LEASE IN TRANSLATION - NOWAK-KORCZ, Paulina (Comparative Legilinguistics, 2014)
This paper deals with Hunting District Lease Agreement in Polish-French and French- Polish translation. The author characterizes the institution of Hunting District Lease in the Polish and French legal systems, distinguishes the typical contractual clauses in both languages Polish and presents the similarities and the differences on the level of the macro- and microstructure of the analyzed texts of agreements which are very important from the translative perspective. In her research the author applies the method of parallel text comparison (Delisle 2006) and the model of pragmatic translation of legal terms described by Kierzkowska (2002) based on the skopos theory of translation by Vermeer (1978, 2001). The examples of translation of the Hunting District Lease Agreement in Polish and French are also presented.